Assessing the Impact of Multimedia Education on Infertility Awareness and Attitudes Among Couples: A Pre-Experimental Study in Vadodara - Pate, Shital; Prakasam, Anita; Patel, Vruti; Patel, Deep; Patel, Dhruta (Journal of Neonatal Surgery, 2025)
Deshpande, P. S., & Gupta, A. S. (2019). Causes and prevalence of factors causing infertility in a public health facility. Journal of Human Reproductive Sciences, 12(4), 287–293. https://doi.org/10.4103/jhrs.JHRS_120_18 Ganguly, S., & Unisa, S. (2010). Trends of infertility and childlessness in India: Findings from NFHS data. Facts, Views & Vision in ObGyn, 2(2), 131–138. Mayer, R. E. (2009). Multimedia learning (2nd ed.). Cambridge University Press. World Health Organization. (2020). Infertility. https://www.who.int/news-room/fact-sheets/detail/infertility Zegers-Hochschild, F., et al. (2017). The International Glossary on Infertility and Fertility Care, 2017. Human Reproduction, 32(9), 1786–1801. https://doi.org/10.1093/humrep/dex234 Authoritative source for definitions and terminologies in fertility care. Patel, T., & Shah, V. (2020). Knowledge and attitude regarding infertility among married women in selected rural area of Vadodara. Indian Journal of Public Health Research & Development, 11(1), 120–124. Directly relevant to your study location; supports knowledge gap data from rural Gujarat. Amoako, J. Y., & Osei, A. (2021). Multimedia health education and behavior change: A review of the literature. International Journal of Health Promotion and Education, 59(2), 55–66. https://doi.org/10.1080/14635240.2020.1809257 Recent literature review supporting multimedia-based health education interventions. Bunting, L., & Boivin, J. (2010). Development and preliminary validation of the fertility status awareness tool: FertiSTAT. Human Reproduction, 25(7), 1722–1733. https://doi.org/10.1093/humrep/deq057 Highlights importance of fertility awareness tools and education. Ali, S., Sophie, R., Imam, A. M., et al. (2011). Knowledge, perceptions and myths regarding infertility among selected adult population in Pakistan: A cross-sectional study. BMC Public Health, 11, 760. https://doi.org/10.1186/1471-2458-11-760